Structural order of water molecules around hydrophobic solutes: length-scale dependence and solute-solvent coupling - Hande, Vrushali R.; Chakrabarty, Suman (Journal of Physical Chemistry B, 2015)
It has been suggested that the structure and thermodynamics of the water molecules in the hydration layer of simple hydrophobic solutes undergo an order disorder transition around a nanometer length-scale of the solute size. Using extensive atomistic molecular dynamics (MD) and replica exchange molecular dynamics (REMD) simulation studies, we have probed this order disorder transition around model hydrophobic solutes of varying size and shape (spherical, planar, and linear), as well as flexible hydrophobic homopolymer chains (n-alkanes), where the conformational fluctuations are likely to create both spatial and temporal heterogeneity on the solvent accessible surface. We have explored the structural response of the water molecules in the hydration shell due to the local variations of the length-scale (or curvature) upon hydrophobic collapse and/or local conformational changes of these polymers. We have shown that the tetrahedral order of the water molecules in the hydration shell is practically independent of the polymer size in the extended state of the polymer due to the availability of a subnanometer cross-sectional length-scale, allowing the water molecules to form hydrogen bonds around the polymer chain. Beyond a certain length of the polymer chains, the collapsed states (associated with larger solute length-scale) start to induce disorder in the surface water molecules. We demonstrate that the local structure (both local number density and tetrahedral order) of the hydration layer is dynamically coupled to the local topology of the polymer. Thus, we envisage that in a flexible (bio)polymer, the hydration shell properties will be sensitive to the local conformational state of the molecule (both spatially and temporally), and the overall observed water structure and dynamics will be dependent on the topological/chemical heterogeneity, and the time-scale of fluctuations in the local curvature (length-scale) of the solvent accessible surface. Moreover, we have demonstrated the direct coupling between the local density fluctuations of water and the local hydrophobic collapse of the polymer. For the extended state of the polymer, the local solvent density fluctuation is practically independent of the solute coordinate (length-scale), and the hydrophobic collapse of the polymer is prompted by a ``local dewetting'' process induced by these fluctuations.

Exploration of the presence of bulk-like water in AOT reverse micelles and water-in-oil nanodroplets: the role of charged interfaces, confinement size and properties of water - Hande, Vrushali R.; Chakrabarty, Suman (Physical Chemistry Chemical Physics, 2016)
The properties of water in a confined environment can be drastically different than the bulk water. In a confined system, e.g. the interior of a reverse micelle, there exist at least two distinct regions namely ``interfacial water'' characterized by markedly slower dynamics, and ``core water'', which may resemble bulk water for a larger size of the water pool. Using atomistic molecular dynamics simulations, we systematically investigate the presence of bulk-like water in AOT reverse micelles (RMs) with varying size given by w(0) = [H2O]/[AOT] = 10, 15 and 20. In order to understand the effect of the negatively charged interface of the RM, we have performed control studies for the model systems of water-in-oil (isooctane) nanodroplets with the same size of the water pool as the RM systems. In order to quantify the deviations from bulk-like behavior, we have used three kinds of structural order parameters, namely (i) number density to probe the local translational ordering, (ii) tetrahedral order and hydrogen bond distribution to probe the local orientational ordering, and (iii) dipolar orientation relative to the radial vector to capture the global orientational ordering of the water dipoles. We demonstrate that the size of the ``core water'' region that resembles bulk water decreases in the above order, i.e. orientational order parameters of water molecules are perturbed by the charged interface to a larger length scale as compared to the translational order. We have compared the translational and rotational dynamics of the water molecules for the interfacial and core regions to find that the slower dynamics persists even for the core water for the size range that we have studied although to a much lesser extent as compared to the interfacial water. Moreover, we demonstrate that the hydrophobic interface in the water-in-oil nanodroplets has a much weaker effect on the structure and dynamics of the confined water molecules as compared to the anionic RMs. Thus, the major contribution towards the structural ordering and slow dynamics of water in a charged RM system would originate from the strong electrostatic and hydrogen bonded interactions with the interface, and not due to the spatial confinement effect.

Effect of sodium dodecyl sulfate surfactant on methane hydrate formation: a molecular dynamics study - Choudhary, Nilesh; Hande, Vrushali R.; Roy, Sudip; Chakrabarty, Suman; Kumar, Rajnish (Journal of Physical Chemistry B, 2018)
In experimental studies, it has been observed that the presence of sodium dodecyl sulfate (SDS) significantly increases the kinetics of hydrate formation and the final water-to-hydrate conversion ratio. In this study, we intend to understand the molecular mechanism behind the effect of SDS on the formation of methane hydrate through molecular dynamics simulation. Hydrate formation conditions similar to that of laboratory experiments were chosen to study hydrate growth kinetics in 1 wt % SDS solution. We also investigate the effect of interactions with isolated SDS molecules on methane hydrate growth. It was observed that the hydrophobic tail part of the SDS molecule favorably interacts with the growing hydrate surface and may occupy the partial hydrate cages while the head groups remain exposed to water.

How far is ``Bulk Water'' from interfaces? depends on the nature of the surface and what we measure - Hande, Vrushali R.; Chakrabarty, Suman (Journal of Physical Chemistry B, 2022)
Using systematic molecular dynamics (MD) simulations, we revisit the question: At what distance from an interface do the properties of ``bulk water'' get recovered? We have considered three different kinds of interfaces: nonpolar (hydrophobic; isooctane-water interface), charged (negative; AOT bilayer), and polar (zwitterionic; POPC bilayer). In order to interrogate the extent of perturbation of the interfacial water molecules as a function of the distance from the interface, we utilize a diverse range of structural and dynamical parameters. To capture the structural perturbations, we look into local density (translational order), local tetrahedral order parameter, and dipolar orientation of the water molecules. We also explore the anisotropic diffusion of the water molecules in the direction perpendicular to the interface as well as the planar diffusion parallel to the interface in a distance dependent manner. In addition, the orientational time correlation functions have been computed to understand the extent of slowdown in the rotational dynamics. As expected, the electrostatic field emanating from the charged AOT interface seems to have the highest long-range effect on the orientational order and dynamics of the water molecules, whereas specific interactions like hydrogen bonding and electrostatic interaction lead to significant trapping and kinetic slowdown for both AOT and POPC (zwitterionic) very close to the interface. Our analysis highlights that not only the length-scale of perturbation depends on the nature of the interfaces and specific interactions but also the type of water property that we measure/calculate. Different water properties seem to have widely different length-scale of perturbation. Orientational order parameters seem to be perturbed to a much longer length-scale as compared to translational order parameters. The global orientational order of water can be perturbed even up to similar to 4-5 nm near the negatively charged AOT surface in the absence of any extra electrolyte. This observation has significant implication toward the interpretation of experimental measurements as well since different spectroscopic techniques would probe different parameters or water properties with possible mutual disagreement and inconsistency between different types of measurements. Thus, our study provides a broader and unifying perspective toward the aspect of ``context dependent'' structural and dynamical perturbation of ``interfacial water''.